Logical Intelligence and Mathematical Competence Are Determined by Physical Fitness in a Sample of School Children - Bracero-Malagón, José; Juárez-Ruiz de Mier, Rocío; Reigal, Rafael E.; Caballero-Cerbán, Montserrat; Hernández-Mendo, Antonio; Morales-Sánchez, Verónica (Frontiers in Psychology, 2022)
Previous research has shown positive relationships between fitness level and different cognitive abilities and academic performance. The aim of this study was to analyze the relationships among logical-mathematical intelligence and mathematical competence withphysical fitness in a group of pre-adolescents. Sixty-three children (50.79% girls; 49.21% boys) from Castro del Río (Córdoba, Spain), aged between 11 and 12 years (M= 11.44, SD= 0.64), participated in this research. The Superior Logical Intelligence Test (SLIT) and the EVAMAT 1.0 - 5 battery were used. Physical fitness was evaluated by the horizontal jump test, the 4x10 meter speed-agility test and the Course Navette test. The analyses showed positive relationships between physical fitness with logical-mathematical intelligence and mathematical competence. These results are in agreement with previous research, highlighting the importance of improving physical fitness from an early age due to its benefits for intellectual and academic development.